Whole genome sequence of Treponema pallidum ssp. pallidum, strain Mexico A, suggests recombination between yaws and syphilis strains - Pětrošová, Helena; Zobaníková, Marie; Čejková, Darina; Mikalová, Lenka; Pospíšilová, Petra; Strouhal, Michal; Chen, Lei; Qin, Xiang; Muzny, Donna M; Weinstock, George M; Šmajs, David (PLoS neglected tropical diseases, 2012)
BACKGROUND: Treponema pallidum ssp. pallidum (TPA), the causative agent of syphilis, and Treponema pallidum ssp. pertenue (TPE), the causative agent of yaws, are closely related spirochetes causing diseases with distinct clinical manifestations. The TPA Mexico A strain was isolated in 1953 from male, with primary syphilis, living in Mexico. Attempts to cultivate TPA Mexico A strain under in vitro conditions have revealed lower growth potential compared to other tested TPA strains. METHODOLOGY/PRINCIPAL FINDINGS: The complete genome sequence of the TPA Mexico A strain was determined using the Illumina sequencing technique. The genome sequence assembly was verified using the whole genome fingerprinting technique and the final sequence was annotated. The genome size of the Mexico A strain was determined to be 1,140,038 bp with 1,035 predicted ORFs. The Mexico A genome sequence was compared to the whole genome sequences of three TPA (Nichols, SS14 and Chicago) and three TPE (CDC-2, Samoa D and Gauthier) strains. No large rearrangements in the Mexico A genome were found and the identified nucleotide changes occurred most frequently in genes encoding putative virulence factors. Nevertheless, the genome of the Mexico A strain, revealed two genes (TPAMA_0326 (tp92) and TPAMA_0488 (mcp2-1)) which combine TPA- and TPE- specific nucleotide sequences. Both genes were found to be under positive selection within TPA strains and also between TPA and TPE strains. CONCLUSIONS/SIGNIFICANCE: The observed mosaic character of the TPAMA_0326 and TPAMA_0488 loci is likely a result of inter-strain recombination between TPA and TPE strains during simultaneous infection of a single host suggesting horizontal gene transfer between treponemal subspecies.
Keywords: syfilis; Treponema pallidum; DNA, Bacterial; Genome, Bacterial; Molecular Sequence Data; Humans; Yaws; Open Reading Frames; Sequence Analysis, DNA; otevřené čtecí rámce; Syphilis; syntenie; DNA bakterií; mužské pohlaví; Recombination, Genetic; frambézie; molekulární sekvence - údaje; Mexiko; rekombinace genetická; sekvenční analýza DNA; genom bakteriální; lidé; Mexico; Male; Synteny